A comparison of the effects of four ergot derivatives on prolactin secretion by dispersed rat pituitary cells. - Delitala, G; Yeo, T; Grossman, A; Hathway, N; Besser, G (1980)
The inhibitory effects of dopamine and various ergot alkaloids on prolactin secretion were studied using continuously perfused columns of dispersed rat anterior pituitary cells. Bromocriptine (5 nmol/l) and lisuride hydrogen maleate (5 nmol/l) both inhibited prolactin secretion, the effects persisting for more than 3 h after the end of the administration of the drugs. A similar although less long-lasting effect was observed with lergotrile (50 nmol/l) and the new ergoline derivative, pergolide (5 nmol/l). These effects contrasted with the rapid disappearance of the action of dopamine. The potency estimates of the ergots relative to that of dopamine were: lergotrile, 2.3; bromocriptine, 13; lisuride, 15; pergolide, 23. Ther dopamine-receptor blocking drugs, metoclopramide and haloperidol, antagonized the prolactin release-inhibiting activity of the compounds; bromocriptine and lisuride showed the highest resistance to this dopaminergic blockade. The results suggested that the direct effect of the ergot derivatives on dispersed pituitary cells was mediated through dopamine receptors and emphasized the long-lasting action of bromocriptine and lisuride in vitro.